2022
DOI: 10.1055/s-0042-1756148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hormonal and Nonhormonal Approaches to Vaginal Atrophy and Sexual Dysfunctions in Postmenopausal Women: A Systematic Review

Abstract: Objective To evaluate the efficacy of the hormonal and nonhormonal approaches to symptoms of sexual dysfunction and vaginal atrophy in postmenopausal women. Data Sources We conducted a search on the PubMed, Embase, Scopus, Web of Science, SciELO, the Cochrane Central Register of Controlled Trials (CENTRAL), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases, as well as on clinical trial databases. We analyzed studies published between 1996 and May 30, 2020. No language re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…The most reported sexual symptom is vaginal dryness (more than 50%), followed by dyspareunia and reduced libido, which are considered the strongest predictors of discontent concerning the decision to undergo RRSO. It was also reported that premenopausal women undergoing riskreducing surgery experience a greater decline in sexual function than post-menopausal women [20,21].…”
Section: Gynecologic Consequences Of Rrsomentioning
confidence: 97%
“…The most reported sexual symptom is vaginal dryness (more than 50%), followed by dyspareunia and reduced libido, which are considered the strongest predictors of discontent concerning the decision to undergo RRSO. It was also reported that premenopausal women undergoing riskreducing surgery experience a greater decline in sexual function than post-menopausal women [20,21].…”
Section: Gynecologic Consequences Of Rrsomentioning
confidence: 97%
“…Lubrificantes e hidratantes de longa duração podem ajudar a aliviar os sintomas quando necessário, porém não tratam a condição atrófica da região em questão. Estes apresentam um menor impacto do que os estrogênios (Sarmento et al, 2022).…”
Section: Métodos Utilizados Para Tratamentounclassified
“…Hormone replacement therapy is often considered the most effective treatment for alleviating vasomotor symptoms and sexual changes in menopausal women. However, there is a portion of women who cannot benefit from this treatment, and although the true effectiveness of other methods is still not fully understood, some of them have shown improvements in symptoms with mild to moderate adverse effects, without serious ones (SARMENTO et al, 2023).…”
Section: Benefits and Risks Associated With Hormone Therapymentioning
confidence: 99%
“…When started late, hormone therapy has a negative effect on cognitive function, increasing the risk of Alzheimer's (METHA et al, 2021). For women who have contraindications, especially those with firstdegree relatives with a history of breast cancer, other treatment options may be considered, such as the use of vaginal lubricants and moisturizers, phytoestrogens, ospemifene, pelvic floor muscle exercises, oxytocin, CO2 laser in the vaginal region, lidocaine, and vitamin E vaginally (SARMENTO et al, 2023).…”
Section: Benefits and Risks Associated With Hormone Therapymentioning
confidence: 99%